2018
DOI: 10.15282/ijame.15.3.2018.9.0424
|View full text |Cite
|
Sign up to set email alerts
|

Kinematics and Injury Analysis of Front and Rear Child Pillion Passenger in Motorcycle Crash

Abstract: The purpose of this work is to study the kinematics and injury of child pillion passenger from motorcycle-to-car crash tests. Two crash tests for rear and front child pillions were set up. The kinematics of dummies were analysed from accelerometer data and high speed camera pictures. The kinematics and injury mechanisms of the child passenger from both tests are significantly different. For the rear child pillion test, the rider impacted the car before the child passenger. Both rider and child were ejected upw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…The child pillion passenger was also included in the model because the accident data showed a significant number of child pillion passengers ( Figure A4) in motorcycle accidents. First the impact configuration was set to be the same as that in the experiment of Koetniyom et al (2018). The motorcycle was set to impact the car at 42.2 km/h.…”
Section: Multibody Motorcycle-car Collision Model Setupmentioning
confidence: 99%
“…The child pillion passenger was also included in the model because the accident data showed a significant number of child pillion passengers ( Figure A4) in motorcycle accidents. First the impact configuration was set to be the same as that in the experiment of Koetniyom et al (2018). The motorcycle was set to impact the car at 42.2 km/h.…”
Section: Multibody Motorcycle-car Collision Model Setupmentioning
confidence: 99%
“…They accounted for 74% of traffic deaths as reported by the World Health Organization in 2018 [1]. Motorcycle accident analysis in Thailand has gained more interest from many researchers over the past 4 years [2][3][4][5][6][7][8][9][10] in order to suggest the development of countermeasures for reducing motorcycle crashes and fatalities [11,12]. Champahom et al [10] recently investigated factors affecting the severity of motorcycle accidents.…”
Section: Introductionmentioning
confidence: 99%
“…Child pillion passengers were among the road accident victims. Koetniyom et al [2] performed motorcycle crash tests with a child pillion passenger behind and before the rider to study the kinematics of the rider and passenger. Their results revealed that the child sitting at the back of the rider had a higher risk of severe head injury, while the child sitting in front of the rider had a higher risk of thorax and neck injury.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation